Incidence and influencing factors of progressive pulmonary fibrosis in connective tissue disease-associated interstitial lung disease: a systematic review and meta-analysis - Yi, Mingyang; Li, Minghao; Zhang, Zhen; Li, Haixia; Sai, Junting; Gui, Yinzhe; Wang, Zhiwan (Frontiers in Immunology, 2026)
BackgroundProgressive pulmonary fibrosis (PPF) is a major cause of poor prognosis in connective tissue disease-associated interstitial lung disease (CTD-ILD). This study aims to analyze and evaluate the incidence of PPF and related influencing factors in CTD-ILD.MethodsWe searched PubMed, EMBASE, the Cochrane Library, Web of Science, and Scopus databases for studies on the incidence of PPF and influencing factors in CTD-ILD until August 20, 2025. The methodological quality of the included studies was assessed using the Newcastle-Ottawa Scale (NOS). Meta-analysis was performed using Stata 17.0 software.ResultsA total of 22 studies were included in the meta-analysis, comprising 20 high-quality studies and 2 medium-quality studies. The incidence of PPF in CTD-ILD was 29% (95% CI: 25% - 34%). Meta-analysis identified Krebs von den Lungen-6 (KL-6: OR = 2.21, 95% CI: 1.24 - 3.94), human Surfactant Protein D (hSP-D: OR = 1.48, 95% CI: 1.16 - 1.90), Matrix Metalloproteinase-7 (MMP-7: OR = 1.48, 95% CI: 1.13 - 1.93), and Cancer Antigen 125 (CA-125: OR = 1.19, 95% CI: 1.05 - 1.34) as risk factors for PPF development. A higher baseline forced vital capacity percentage predicted value (FVC% predicted: OR = 0.98, 95% CI: 0.96 - 0.99) was identified as a protective factor against PPF development.ConclusionsPatients with CTD-ILD are at high risk of developing PPF, and this progression risk is associated with KL-6, hSP-D, MMP-7, and CA-125. Identifying the incidence risk and influencing factors of PPF in CTD-ILD is crucial for early identification of high-risk populations, optimizing diagnostic and therapeutic strategies, and improving prognosis.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251128274.